Client satisfaction with services provided at the antenatal care centres of BRAC - Afsana, Kaosar; Chowdhury, Amr (BRAC Research and Evaluation Division (RED), 2019)
BRAC has implemented the Women's Health and Development Programme (WHDP) in the northern and central rcgi.oni of Bangladesh to reduce maternal and child death. Among the various components of the programme, organization of antenatal care centres (ANCC) is an important activity. This study measured satisfaction of the pregnant with the services provided at the ANCCs in three thanas ofBogra region. A total of 33 ANCCs was observed for a study which assessed competence of the programme organizers (POs ). Two pregnant women who received services from the 33 ANCCs were randomly selected. Following their attendance at the ANCCa, women were interviewed at home by the experienced field workers to know their satisfaction with services. Field activities were carried out Wlder meticulous supervision of a medical doctor. Client satisfaction was measured by focusing on eight quality aspects which include overall quality, accessibility, availability, cost, interpersonal relations, competence of the programme organizers (PO), faciJities and continuity of care. Satisfaction was ranked according to the proportion of women satisfied, i.e., higher the proportion more is the rank. Satisfaction ranged from high to low with the eight quality aspects. The overall quality, facilities and accessibilities arc ranked at the top, which are related to the structural quality. The bottom five ranks reflect the process of antenatal care as wen as the socio-psychological factors of the clients. A vast difference was observed . ~ between the top and lowest rank.. It is indicated by the fact that women's satisfaction with the continuity of care (64%) was very low in comparison to satisfaction with the o~ quality (98%). This finding gives some impression about women's view on the quality of care. Further, women put few suggestions in order to improve services offered at the ANCC., such as improvement of the physical facilities, availability of medicine at the ANCC8 and treatment of the • complicated cases. With reference to women's view about the quality and women'a suggestions to improve the services, some recommendations were made to further improve the quality of care. Suggestions inelude women's awareness about pregnancy related problems should be raised through health education as wen as fonnal education; interactions with the clients needs to be strengthened to avail services of the ANCCs and the trained traditional birth attendants (TBAs); the POs should be more skiJlcd in attending the complicated cases; more medicine needs to be available in the ANCCs; rewarding the efforts of the POs and TBAs needs to be considered.